Analysis of Sleep Quality on Performance in U-17 Volleyball Athletes from Kendal Regency Dissporsa Club - Nadira Heranita Prasetya; Sugiarto Sugiarto (Journal of Community Health Provision, 2026)
Sleep is a process that affects almost all body systems, such as the neurological, immune, cardiovascular, and endocrine systems. During sleep, the body produces ATP, which serves as the body's energy source. Energy is needed for muscle contraction so the body can carry out daily activities. This study was conducted to determine whether sleep quality affects performance and whether there is a relationship between the two variables. The data collection method used was filling out the PSQI questionnaire and conducting MFT. The sampling technique used was purposive sampling. Data analysis was carried out using SPSS 22, by conducting normality tests, linearity tests, and correlation tests. The subjects in this study were 15 U-17 athletes from the Dissporsa club. The results showed that 11 athletes had "good" sleep quality and 4 others had "poor" sleep quality. 6 athletes had "very good" endurance, 7 others were in the "good" category, and the remaining 2 were in the "moderate" category. Based on the results of the correlation test, it was known that the Sig. value was 0.011 (p <0.05) with a correlation coefficient value of 0.635. Therefore, it can be concluded that sleep quality and performance have a very strong, significant relationship.